2019
DOI: 10.3390/jcm8060821
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience in CT-Guided Percutaneous Transthoracic Needle Biopsy of Lung Lesions Performed by a Pulmonologist

Abstract: In the diagnosis of lung lesions, computed tomography (CT)-guided percutaneous transthoracic needle biopsy (PTNB) has a high diagnostic yield and a low complication rate. The procedure is usually performed by interventional radiologists, but the diagnostic yield and safety of CT-guided PTNB when performed by pulmonologists have not been evaluated. A retrospective study of 239 patients who underwent CT-guided PTNB at Yeungnam University Hospital between March 2017 and April 2018 was conducted. A pulmonologist p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…However, there are also some complications after percutaneous lung biopsy and the COPD patients should be paid more attention to the risk of pneumothorax. Previous literature reported that incidence rates of pneumothorax were 12.0%‐45.0% and 2%‐15.0% of chest tube placement rate to cope with pneumothorax 11,22‐24 . In our study, the incidence of pneumothorax after percutaneous pulmonary puncture in the total population was 21.5% and that of pneumothorax requiring closed drainage was about 3.2%, which was accepted.…”
Section: Discussionsupporting
confidence: 62%
“…However, there are also some complications after percutaneous lung biopsy and the COPD patients should be paid more attention to the risk of pneumothorax. Previous literature reported that incidence rates of pneumothorax were 12.0%‐45.0% and 2%‐15.0% of chest tube placement rate to cope with pneumothorax 11,22‐24 . In our study, the incidence of pneumothorax after percutaneous pulmonary puncture in the total population was 21.5% and that of pneumothorax requiring closed drainage was about 3.2%, which was accepted.…”
Section: Discussionsupporting
confidence: 62%
“…However, the use of ROSE in this process can provide real-time guidance, improve diagnostic accuracy, reduce the risk of operation, and avoid unnecessary harm. ROSE should be applied to CT-guided FNA [11,[13][14][15][16][17][18][19]. Some studies indicate that the success of ROSE requires an experienced and united team; otherwise, more time will be wasted [15,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CT scan has good contrast and resolution, which can clearly display the morphology, size, and adjacent important structure of lesions and can display small lesions beside the mediastinum, behind the heart shadow, and beside the spine [ 15 , 16 ]. It has been reported that the accuracy of CT-guided lung biopsy in the diagnosis of benign lesions is >80% and that of malignant lesions is >90% [ 17 ]. In this study, the diagnostic efficiency of multislice spiral CT for pulmonary nodules of different sizes was observed.…”
Section: Discussionmentioning
confidence: 99%